PENGARUH PERSEPSI DAN PREFERENSI MASYARAKAT TERHADAP KEPUTUSAN PEMBELIAN PERUMAHAN SYARIAH DI KABUPATEN BEKASI - Aryandhana, Dea; Bintarti, Surya; Hidayatullah, Refangi (Jurnal Ekonomi Syariah Pelita Bangsa, 2021)
The development of the sharia economy is now increasing, which can be seen from the increasing number of sharia financial institutions and sharia business institutions. This has an impact on people's understanding of interest and capital whose results have been determined in advance (predetermined return) which is usury which is prohibited by Islamic sharia. This positive trend in Sharia mortgages is also reflected in the results of the rumah.com Consumer Sentiment Study H2 2020 survey, where there was an increase in consumer preferences for choosing Sharia mortgages to 35% of respondents at the beginning of the second semester of 2020 from 29% of respondents in the first semester of 2020. On the other hand, conventional mortgage enthusiasts have decreased from 37% compared to the first semester of 2020. Sharia mortgages are the preference of rumah.com Consumer Sentiment Study H2 2020 respondents with the main reason being the certainty of the amount of monthly installments (fixed rate) stated by 74% of respondents. This means that the majority of people's considerations choose sharia mortgages because of economic considerations.Based on the results of research on the effect of public perceptions and preferences on purchasing decisions for sharia housing in Bekasi Regency, it can be concluded that: first, public perceptions as consumers have a moderate positive effect (35%) on the level of purchasing decisions. The low role of this perception is due to many consumer perceptions that do not match consumer experience, and when consumers decide to buy sharia products, the budget funds that must be spent are larger than buying a house with a conventional concept. Second, the public's preference as a consumer has a fairly strong significant effect (65%) on the level of purchasing decisions. The role of preference is quite strong because of the knowledge or information that people understand is that Islamic housing is always better than conventional housing.